Acetylcholinesterase inhibition test by caulerpa lentillifera and caulerpa racemosa / Noorezzatul Shahira Mohd Zamri - Mohd Zamri, Noorezzatul Shahira (2020)
Alzheimer disease (AD) is the one common type causes of dementia and neurogenerative disease. It has occurred when the chemical messenger or neurotransmitter in the brain are unable to transmit the signal from one neuron cell to another through the synaptic cleft. Thus, a person who is suffering AD will be unable to do the normal activities such as lack of mathematical skill, memorize some notes and others. Nowadays, the drugs that consume by the patient only relieve the symptom of the disease, which is by inhibit the acetylcholinesterase enzyme (AChE). As the result, the acetylcholine (ACh) level will be increasing. However, it gives a side effect to the patient. In this study, the natural resources are being used for AD treatment by inhibit the AChE enzymes. Generally, there are a lot of previous research that give more attention to red and brown seaweed and lack uses of green seaweed which have the potential that may not have exposed to the public. Especially Caulerpa lentillifera and Caulerpa racemosa which are popular in seafood dish serving. The objective of this study is to evaluate and determine the AChE inhibitory effect of C. lentillifera and C. racemosa extract through TLC plate test and using Ellman method, and to identify the chemical constitution of C. lentillifera and C. racemosa extract using GC-MS. In TLC plate test, the silica gel TLC plate have been used and the sample extraction are tested on AChE enzyme to give the result of white spot effect as well as inhibitory activities. Moreover, to improve the inhibitory activities are by using microplate reader and the inhibition are read by percentage. For chemical constitution, both samples are used to identify the bioactive compound that might available. As the result, for the TLC plate test, both samples are given the positive result as referred by positive control which is Eserine. In Ellman method, the C. racemosa are much higher inhibition percentage than C. lentillifera where about 54.45% in C. racemosa and 52.70% in C. lentillifera by mean at 10mg/ml of concentration. For chemical constitution, only a few compounds that are identified as potential biological activities. As a conclusion, the potential of AChE inhibition activity by Caulerpa lentillifera and Caulerpa racemosa are giving the high chance to be nutraceutical production.